Simultaneous quantification of l‐tetrahydropalmatine and its urine metabolites by ultra high performance liquid chromatography with tandem mass spectrometry. Issue 6 (19th February 2014) - Xiao, Weibin; Zhuang, Xiaomei; Shen, Guolin; Zhong, Yuhuan; Yuan, Mei; Li, Hua
<x xml:space="preserve">Abstract</x> l‐tetrahydropalmatine (l‐THP) is a tetrahydroprotoberberine isoquinoline alkaloid that has been used as an analgesic agent in China for more than 40 years. Recent studies indicated its potential application in the treatment of drug addiction. In this study, a sensitive and rapid method using ultra high performance liquid chromatography with MS/MS was developed and validated for simultaneous quantitation of l‐THP and its desmethyl metabolites. Enzymatic hydrolysis was integrated into sample preparation to enable the quantitative determination of both free and conjugated metabolites. Chromatographic separation was achieved on an Agilent Poroshell 120 EC‐C18 column. Detection was performed by MS in the positive ion ESI mode. The calibration curves of the analytes were linear (r2 > 0.9936) over the concentration range of 1–1000 ng/mL with the lower limit of quantification at 1 ng/mL. The precision for both intra‐ and interday determinations was <8.97%, and the accuracy ranged from −8.74 to 8.65%. The recovery for all the analytes was >70% without significant matrix effect. The method has been successfully applied to the urinary excretion study of l‐THP in rats. The conjugates were found to be the major urine metabolites of the drug.